Higher Education Research & Development Perceptions of Gender Dynamics in Pakistani Dramas Among the Younger Generation. - Batool, Syeda Farah; Sarfraz, Sumera; Mirza, Faizan (International Journal on Women Empowerment, 2023)
Background: This study investigates the perceptions of male and female undergraduate and postgraduate students regarding the portrayal of toxic masculinity, misogyny, and abuse in Pakistani television dramas. Pakistani dramas, known for their cultural influence, have faced criticism for reinforcing problematic gender stereotypes. The study, grounded in the recognition of media's impactful role in shaping societal norms, aims to provide insights from the younger generation, both consumers and shapers of cultural narratives. Methodology: A qualitative approach, utilizing semi-structured interviews and focus group discussions was adopted. Purposive sampling strategy ensures diversity among 70 participants, encompassing various genders, academic disciplines, and educational levels. Thematic analysis is employed to derive patterns and themes from participants' responses. Results: The thematic analysis reveals significant findings under three main themes including Perceptions of Gender Roles in Pakistani Dramas, Impact of Media Portrayals on Attitudes and Behaviors and Suggestions for Promoting Healthier Depictions of Relationships. Conclusion: The study emphasizes the crucial role of media in shaping cultural narratives and societal attitudes. The recommendations provided offer actionable steps for fostering a more inclusive and equitable media environment. As media continues to wield considerable influence, responsible navigation of narratives is essential for promoting a healthier society.